Energy and rate modeling of data download over LTE with respect to received signal characteristics - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
Estimating energy consumption and data rate in LTE networks is a critical issue for some recently proposed applications such as collaborative Internet access and energy-aware cellular data scheduling. In this study, after collecting data via empirical measurements, we provide realistic modeling with respect to LTE signal parameters such as RSRP, RSRQ and SINR. We applied various regression methods after careful data analysis and appropriate transformations to avoid biased estimations. We provide several formulas for energy and throughput estimations, and analyze their goodness of fit values. Resulting models could be utilized in current applications as well as they would provide a benchmark to compare energy efficiency of new studies in the context of upcoming 5G networks and beyond. © 2017 IEEE.
Keywords: Data Rate Modeling; Energy Modeling; LTE